Fabrication and Characterization of Direct Recycled Al-Cu-Cullet Metal Composite - Nuhu, Awwal Hussain; Jikan, Suzi Salwah; Asman, Saliza; Badarulzaman, Nur Azam; Muhammad Zago, Dagaci; Bano, Nazia (Journal of Science and Technology, 2017)
A composite is any material which consist of two or more components of different phases and with different and superior than those of any of the original materials. In the present work, Aluminium (Al) composites were fabricated from direct recycle of Aluminium scrap from door and window frames, used copper (Cu) wires and cullet powder (CP) using stir casting method. The processing parameter of these composites were only varied in their holding time during casting process. The composites and the matrix alloy were analysed for mechanical properties as well as for their chemical composition. The mechanical property, hardness, of the composites in addition to some physical properties such as density was found to have enhanced in the product. The fabricated composites were analysed using energy dispersive x-ray spectroscopy (EDX) and results have shown ascertained that the chemical composition of the product comprising all the components while X-ray Diffraction (XRD), results confirmed qualitatively, the chemical structures of the elemental components. The tests results indicated that the Al-Cu-CP metal matrix composites (MMCs) had shown higher degree of hardness along with density than the unreinforced matrix.